Modifying the Glycocalyx of Melanoma Cells via Metabolic Glycoengineering Using N-Acetyl-d-glucosamine Analogues - Harris, David; Groß, Marcel; Stäbler, Sebastian; Ebert, Regina; Seibel, Jürgen; Boßerhoff, Anja Katrin (Cells, 2024)
Tumor cells are decorated with aberrant glycan structures on cell surfaces. It is well known that the glycocalyx serves as a main cellular regulator, although its role in cancer is still not completely understood. Over recent decades, several non-natural monosaccharides carrying clickable groups have been introduced in melanoma cells. This technique, called Metabolic Glycoengineering (MGE), opens up the possibility of altering the cell’s glycocalyx via click chemistry using a two-step approach. This study expands the field of MGE by showing the successful metabolic incorporation of novel alternative artificial glucosamine derivatives. The latter were either deoxygenated or blocked by methyl ether in position 4 to generate deficient glycosylation patterns, while being extended by an alkyne to enable click chemistry as a one-step approach. As a result, we observed a reduced proliferation rate of melanoma cells. Furthermore, using a lectin array, the decrease in high mannose epitopes was observed. In summary, the successful use of alternative artificial glucosamine derivatives enabled a significant alteration in the glycocalyx, consequently influencing cell behavior.
CRIS-Team Scopus Importer:2024-12-06
Keywords: click chemistry; glycoproteins; melanoma cells; metabolic glycoengineering